2010
DOI: 10.1007/s10457-010-9312-0
|View full text |Cite
|
Sign up to set email alerts
|

Root length density and carbon content of agroforestry and grass buffers under grazed pasture systems in a Hapludalf

Abstract: Enhancement of root development helps to improve soil physical properties, carbon sequestration, and water quality of streams. The objective of this study was to evaluate differences in root length density (RLD) and root and soil carbon content within grass buffer (GB), agroforestry buffer (AgB), rotationally grazed pasture (RG) and continuously grazed pasture (CG) treatments. Pasture and GB areas included red clover (Trifolium pretense L.) and lespedeza (Kummerowia stipulacea Maxim.) planted into fescue (Fest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 52 publications
0
18
0
4
Order By: Relevance
“…Better soil physical quality observed in CLF or CL may be attributed to soil resilience and restoration by wetting and drying cycles and root growth (Gregory et al, 2007). The CL (soybean and palisade) and CLF (eucalypt, soybean and palisade) systems with greater species diversity may have a better root system (Kumar et al, 2010), with a beneficial impact on soil physical quality. Silva et al (2011) observed that two years is an optimum time for management of a crop-livestock system for improving soil physical properties.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Better soil physical quality observed in CLF or CL may be attributed to soil resilience and restoration by wetting and drying cycles and root growth (Gregory et al, 2007). The CL (soybean and palisade) and CLF (eucalypt, soybean and palisade) systems with greater species diversity may have a better root system (Kumar et al, 2010), with a beneficial impact on soil physical quality. Silva et al (2011) observed that two years is an optimum time for management of a crop-livestock system for improving soil physical properties.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…Lal (2004) reported that integration of crop, livestock and forest (agroforestry) systems can accentuate SOC sequestration. Increases in the SOC concentration and pool through the use of agroforestry systems, as reported by Paudels et al (2012) in subtropical regions, as well as in some soils of tropical regions (Lima et al, 2011), have been attributed to higher root densities (Kumar et al, 2010),. However, most agroforestry studies involve fruit trees rather than timber wood species.…”
Section: Introductionmentioning
confidence: 95%
“…Plant residues were not removed while inserting the ring. At the time of infiltration measurements, gravimetric soil water content at depths of 0-10, 10-20, and 20-30 cm was taken in the area surrounding the ring from all treatments and adjusted to volumetric water content using the bulk density values extracted from Kumar et al (2010b).…”
Section: Ponded Infiltration Measurementsmentioning
confidence: 99%
“…The fitted a parameters were averaged for 0-10 and 10-20 cm depths for AgB, GB, RP and CP treatments. Saturated hydraulic conductivity (K sat ) values were obtained from Kumar et al (2010b) for comparison with field K fs values.…”
Section: Ponded Infiltration Measurementsmentioning
confidence: 99%
See 1 more Smart Citation